2004
DOI: 10.4326/jjcvs.33.382
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evaluation of the Biocompatibility and Cytotoxicity of Local Hemostatic Agents

Abstract: When local hemostatic agents are used in surgery, rapid dissolution followed by prompt absorption without adverse effect after successful hemostasis are essential qualities. Residual hemostatic materials greatly influence host cells during the wound healing process. Biocompatibility of material is also essential. Furthermore, hemostatic agents also should be free of cytotoxicity that may block mitosis and migration of host cells, so that wound healing can proceed smoothly. For the evaluation of biocompatibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…34 The ideal hemostatic agents also should be free of cytotoxicity, but the ability of hemostasis is more important; however, after hemostasis is achieved, unused hemostatic material should be eliminated, leaving as little hemostatic agent as possible in order to avoid postoperative complications. 35 Odabas et al studied that ABS was cytotoxic to human pulp fibroblasts by MTT (3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide, a yellow tetrazole) assay. The influence of cytotoxicity to human pulp fibroblasts depended on the concentration of ABS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The ideal hemostatic agents also should be free of cytotoxicity, but the ability of hemostasis is more important; however, after hemostasis is achieved, unused hemostatic material should be eliminated, leaving as little hemostatic agent as possible in order to avoid postoperative complications. 35 Odabas et al studied that ABS was cytotoxic to human pulp fibroblasts by MTT (3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide, a yellow tetrazole) assay. The influence of cytotoxicity to human pulp fibroblasts depended on the concentration of ABS.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal hemostatic agents also should be free of cytotoxicity, but the ability of hemostasis is more important; however, after hemostasis is achieved, unused hemostatic material should be eliminated, leaving as little hemostatic agent as possible in order to avoid postoperative complications. 35…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the mean clinical and radiographic success rates of pulpotomy treatment with ferric sulphate were 91.6 % and 73.5 %, respectively. The ideal hemostatic agents also should be free of cytotoxicity, but the ability of hemostasis is more important; however, after hemostasis is achieved, unused hemostatic material should be eliminated, leaving as little hemostatic agent as possible in order to avoid postoperative complications (29). Moreover, it should be discussed into a broader perspective that many materials such as peroxides for dental bleaching and bonding agents used in adhesive dentistry all demonstrate cytotoxicity in vitro (30), yet they form an important part of every dentist's restorative armamentarium.…”
Section: Discussionmentioning
confidence: 99%
“…Acidic products may provoke a strong inflammatory response at the implanted site and slow down the healing process (Ibarrola et al 1985; Krishnan et al 2004; Meric et al 2016). In addition, studies have shown that other ORC products, made from different materials than the studied product, are not entirely biodegradable for as long as 5 weeks after implantation (Tamargo et al 1989; Alpaslan et al 1997; Ibrahim et al 2002; Tomizawa 2004).…”
Section: Discussionmentioning
confidence: 99%